Feasibility Study of Simultaneous Measurement of Multiple Parameters from a Single Monolithic Scintillator Crystal Using the Geant4 Simulation Toolkit. Issue 1 (1st April 2022) - Ivanov, S; Toneva, Zh
Abstract: A feasibility study for the construction of a minimal multi-parameter detector module from a single monolithic CeBr3 scintillator crystal and a SiPM matrix that is capable of simultaneously measuring deposited energy, position of particle interaction and time characteristics was performed by simulation and direct measurements. The results show that the detector module can operate successfully with characteristics that are close to the limits of the physical detector and that such minimal modules can potentially be used on micro- and nano-satellite platforms .